2017
DOI: 10.1136/oemed-2017-104414
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative DNA damage during night shift work

Abstract: This study suggests that night work, relative to night sleep, is associated with reduced repair of 8-OH-dG lesions in DNA and that the effect is likely driven by melatonin suppression occurring during night work relative to night sleep. If confirmed, future studies should evaluate melatonin supplementation as a means to restore oxidative DNA damage repair capacity among shift workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 11 publications
3
21
0
3
Order By: Relevance
“…A previous study has shown that melatonin, which plays a major role in the regulation of the circadian wake-sleep cycle (Ortiz et al 2011), was lower in night shift workers than that of workers without night shift (Bhatti et al 2017). It has also been reported that the urinary melatonin level was positively associated with sperm concentration (Ortiz et al 2011) and the cellular oxidative DNA damage repair capacity (Bhatti et al 2017). The findings of our study and previous studies together suggest a significant association between sleep quality and sperm quality, probably both occurring as a result of disturbed melatonin secretion.…”
Section: Discussionmentioning
confidence: 93%
“…A previous study has shown that melatonin, which plays a major role in the regulation of the circadian wake-sleep cycle (Ortiz et al 2011), was lower in night shift workers than that of workers without night shift (Bhatti et al 2017). It has also been reported that the urinary melatonin level was positively associated with sperm concentration (Ortiz et al 2011) and the cellular oxidative DNA damage repair capacity (Bhatti et al 2017). The findings of our study and previous studies together suggest a significant association between sleep quality and sperm quality, probably both occurring as a result of disturbed melatonin secretion.…”
Section: Discussionmentioning
confidence: 93%
“…34 A previous study showed that the melatonin was higher in workers without night shift, than those with night shift. 35 Another study 36 reported that the melatonin level in urine was positively correlated with sperm concentration. Consistent with these two studies, our findings demonstrated that melatonin and circadian system play an important role in determining male reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…These findings could be related to circadian disruption, which has been linked to dysregulation of gene transcription of the Circadian Locomotor Output Cycles Kaput (CLOCK) genes [22] in which single nucleotide polymorphisms have been linked to reduced semen volume, sperm count, and sperm motility [23]. The disruption of the circadian rhythm has also been associated with lower levels of urinary 8hydroxydeoxyguanosine likely caused by reduced melatonin levels indicating a reduced ability to repair oxidative deoxyribonucleic acid (DNA) damage which is important for fertility [24]. In line with this, Shi et al [13] found a higher DNA fragmentation index (DFI) in men with irregular sleep.…”
Section: Bedtimementioning
confidence: 99%